2019
DOI: 10.4236/jmmce.2019.76032
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Pectin from Ripe Plantain Peel, Fabrication and Characterization of Composite (Pectin/PVA/Glycerol) Films Produced from the Extracted Pectin

Abstract: High methoxyl pectin (DE = 59.53%) was extracted from plantain peel using acid extraction method. Pectin yield was 40.5%; moisture content was 87.56%; equivalent weight was 1000 g/ml, and galacturonic acid content was 2.89 mg/ml. Composite polymer films incorporating the extracted pectin manifest their best mechanical properties; tensile strength and % elongation of 5.51 MPa and 5.75% respectively with 10 ml glycerol/1g pectin. Raman spectra peaks at 2930 cm 1 , 1750 cm −1 and 820 cm −1 indicated CH-stretch, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Moisture levels in all samples were below 20%, and all were below the pectin moisture levels described by Obele et al [26].…”
Section: Proximate Composition Of Extracted Pectinmentioning
confidence: 43%
See 1 more Smart Citation
“…Moisture levels in all samples were below 20%, and all were below the pectin moisture levels described by Obele et al [26].…”
Section: Proximate Composition Of Extracted Pectinmentioning
confidence: 43%
“…Pectin also has applications in the pharmaceutical and biomedical industries as an excipient, drug delivery system, wound healing agent, and anticancer agent [23][24][25]. Obele et al [26] extracted pectin from plantain peels and formulated it into composite flms. Tey found that the extraction methods, form of starting material, and analysis employed afected the physicochemical properties of the pectin flms.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 It is very useful in detecting the target molecular structure and its ngerprint information. Many studies have been carried out on label-free pectin detection using SERS, such as pectin in fruit, 30 tomato tissue, 31,32 plantain peel, 33 and beverages. 30,34 However, the methods proposed in these studies require additional separation procedures and complicated operation.…”
Section: Introductionmentioning
confidence: 99%